Manajemen K3 Perkebunan Kelapa Sawit PT. Bumi Mas Agro, Kalimantan Timur - Ndraha, Samuel; Suswatiningsih, Tri Endar; Purwandari, Istiti (Manajemen Agribisnis: Jurnal Agribisnis, 2025)
This research was conducted at PT. Bumi Mas Agro, Estet Damar which is a company engaged in oil palm plantations. This study aims to, 1) To determine the implementation of occupational safety and health (OS&H) management system in oil palm plantations of PT. Bumi Mas Agro, 2) To find out the obstacles in the implementation of the occupational health and safety management system at PT. Bumi Mas Agro. The method of determining the location using case studies by deliberately choosing the location. The sampling method in this study used purposive sampling, namely taking informants of 1 K3 expert, 1 foreman and respondents of 30 harvest employees. Analysis based on assessment indicators of Government Regulation No. 50 of 2012. The results of this study show the Application of Occupational Safety and Health Management at PT. Bumi Mas Agro in Estate Damar reached 93.4% with the very good category and the company's obstacles to occupational safety and health are: Employee awareness of the overall type of personal protective equipment has not reached 100% and the achievement of zero accident.